Effect of rate of crystallization on the continuous reactive crystallization of nanoscale 6-line ferrihydrite - Loan, M.; Newman, O.; Farrow, J.; Parkinson, Gordon (American Chemical Society, 2008)
Altering the rate of 6-line ferrihydrite continuous reactive crystallization from the control conditions of pH 3.6 and 85 °C was investigated by varying the pH, feed concentration, and mean residence time. In these experiments, the rate of precipitation changed the relative proportion of 6-line ferrihydrite and goethite nanoparticles in precipitates and the aggregates physical properties of surface area, impurity concentration, filtration rate, and particle size. Although increasing the rate of precipitation had a negligible effect on bulk supersaturation, it is thought to locally increase the supersaturation at the FeIII feed inlet and precipitate 6-line ferrihyrdite and for goethite precipitation to occur in the bulk. Alternatively, decreasing the rate of precipitation increased the relative proportion of goethite in precipitates, and the formation of smaller aggregates with higher impurity concentrations and surface areas. A educt on in pH also increased the proportion of goethite in precipitates and reduced the aggregates particle size distribution. The increased solubility at lower pH is believed to promote goethite formation by improved dilution of the feed solution. This work has demonstrated that the physical properties of 6-line ferrihydrite and goethite precipitates can only be altered via the way primary crystals aggregate and not through altering their crystallinity. © 2008 American Chemical Society.